IFRS IMPLEMENTATION, DISCLOSURE AND AUDITOR SWITCHING ON AUDIT DELAY IN MANUFACTURING COMPANY - Luh Komang Merawati; Ni Nyoman Komala Dewi; Ida Ayu Nyoman Yuliastuti (Universitas Multimedia Nusantara, 2022)
Abstract— The submission of audited financial statements of public companies listed on the Indonesia Stock Exchange must meet the requirements of the Financial Services Authority (Bapepam/OJK). The timeliness of submission of audited financial reports is strongly influenced by audit delay or audit completion time. This research aims to know the effect of IFRS implementation, company loss disclosure, auditor switching, internal control system and leverage on audit delay in manufacturing company listed on Indonesia Stock Exchange from 2018 to 2020. Population in this research were 186 company, using a purposive sampling method obtained 161 company, resulted 483 observation for three years. The data analysis technique used was multiple linear regression analysis. The research result was IFRS implementation and company loss disclosure had a positive effect on audit delay, while the internal control system, leverage and auditor switching had no effect on audit delay. Keywords: Audit Delay; Auditor Switching; Disclosure; IFRS; Internal Control System; Leverage.